Tree species composition rather than biodiversity impacts forest soil organic carbon of Three Gorges, southwestern China - Liu, Nan; Wang, Yujie; Wang, Yunqi; Zhao, Zhanjun; Zhao, Yangyi (Nature Conservation, 2016)
Forest soil represents an important resource for mitigating the climate change. Besides, plant composition and diversity and their roles in ecosystem functioning are becoming a central issue in forestsoil organic carbon(SOC) research. The primary objective of this research is to investigate the effects of tree species diversity and composition on potential of C sequestration of forest soil in Three Gorges area and provide basic information to future research on climate change. Two dominant forest ecosystems were selected: mixed conifer-broadleaf forest (Fm) and evergreen broadleaf forest (Fb). Then study transects were established and investigated. Soil samples were collected and determined for bulk density, SOCconcentration and stock, nitrogen (N) concentration and C: N ratio. The results showed that the statistical differences ofSOC concentrations and stocks between Fm and Fb were caused by tree species composition rather than the tree species diversity. And the most significant differences were found in the first two soil horizons (0–15 cm and 15–30 cm). The average C: N values of four different horizons in Fm were decreased with increasing soil depth as well as Fb. Not onlySOC concentrations but also stocks of the two studied forests were decreased with increasing soil depth. However, Fm showed a larger capacity to storeSOC with an average stock of 183.50 t/ha than that of Fb (100.44 t/ha) in study area. Thus, forest which is composed of conifer and evergreen broadleaf tree species may be the best choice for local afforestation and reforestation aimed at alleviating climate change in Three Gorges region.